KEKELUARGAAN SEBAGAI KUNCI PEMAHAMAN PANCASILA - Sudaryanto, Sudaryanto (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2007)
The authentic of Pancasila’s formulation has been agreed as was grafted in the preamble of 1945 constitution. However, the problem of interpretation to Pancasila’s content (sila-sila), whether it is an authentic or not is still emerging many questions. In the regime of New Order there was an effort of Pancasila’s meaning standardization through political decision even though there were many reactions to refuse it. The familial relationship is static aspect and mutual-cooperation is dynamic aspect are always serve as a core or keyword for understanding of Indonesian state system. Pancasila as the foundation of Indonesian state is a part of the system of state. Therefore, the content of Pancasila (sila-sila) should be understood from the angel of familial relationship as its core and keyword. The founding fathers intended to form the state that is based on the Indonesian culture. The life of society based on the Indonesian culture is a familial relationship life. The state that is based on the familial relationship is an integral-state which is powerful than the personal-minded or group’s interest in the way of the integral-state acknowledges the extraordinary of such group.